Effect of Recasted Material Addition on the Quality of Metal-Ceramic Bond: A Macro-, Micro-, and Nanostudy - Karolina Beer–Lech; Krzysztof Pałka; Anna Skic; Barbara Surowska; Krzysztof Gołacki (Advances in Materials Science and Engineering)
Using the recasted alloys in dental prosthetics could affect the quality of the metal-ceramic bond. However, scientists, alloys producers, and prosthetists are still of different opinions. The purpose of this study was to estimate the influence of recasting of the NiCrMo alloy on the metal-ceramic bond quality. The research was carried out on macro-, micro- and nanoscales using the three-point bending test procedure and hardness tests as well as atomic force microscopy and SEM analyses. The SEM analyses showed good integrity of the metal-ceramic bond. The τb index of all test samples was greater than 45 MPa. The highest values were recorded for the samples made of 50% and 100% of a brand new material. SEM analysis made after the bending test confirmed good metal-ceramic bond and exhibited adhesive-cohesive fracture. The largest hardness of metal plates was found for the samples containing 50% of the recycled material. Atomic force microscopy studies showed that the alloy containing 50% of the recycled material was characterized by the highest values of surface roughness parameters.